Smart Home Security System - Akter, Morium; Abu Baker, Mohammad; Shorif Uddin, Mohammad (Transactions on Engineering and Computing Sciences, 2023)
Nowadays, the main concern of people is security. Security is essential not only for the safeguarding of an increasing number of crimes but also for daily accidents. Automated security systems are a wonderful addition to today's home where safety is a major problem. For a comfortable and secure home, appropriate steps would be taken in this present situation through technical innovation. We have developed a security system using sensors to detect any security breaches and send a warning signal via a buzzer of high intensity, flashing red lights, sending messages, and calling the phone of the house owner. For the detection of gas leakage in the house, the system has used a gas sensor. It also has smoke and fire sensors to guard against a fire blast in the house. Our system has features for the detection of intrusion by using a passive infrared sensor (PIR sensor). It also has a sound sensor to detect massive sounds and a temperature sensor to detect the high temperature in the house. All of the mentioned sensors are properly connected to a centralized Arduino Uno microcontroller board which will produce a correct output in case of any tragedy.